A new congestion control algorithm for active networks - Buhari, Seyed Mohamed; Habaebi, Mohamed Hadi; Mohd Ali, Borhanuddin (Universiti Putra Malaysia Press, 2005)
This paper discusses and analyses different congestion control schemes for active networks and proposes a new one. The proposed scheme strikes a balance between the number of errors considered and the waiting time before taking action. The scheme implemented works on "Choke packet" concept, where the source is instructed to reduce the transmission rate. Reasonable reduction of transmission rate is maintained at the source as the intermediate nodes in active networks platform take actions instead of the usually acting destination nodes. The proposed scheme was simulated using OPNET and simulation results are reported. Results indicate that the source-quenching technique implemented in the intermediate nodes of the active network reduces congestion drastically and improves overall network performance.